Result Of Pars Plana Vitrectomy In Post Traumatic Endophthalmitis (Indian Journal of Applied-Basic Medical Sciences, 2021)
Aim: To evaluate visual outcomes and identify prognostic factors after pars plana vitrectomy (PPV) surgery for  traumatic endophthalmitis. Methods: Medical records of 20 patients diagnosed with traumatic endophthalmitis that had undergone pars plana  vitrectomy were retrospectively reviewed. Result: 20 patients all underwent PPV surgery.50% of them obtained BCVA better than fingers counting (FC). Good  final visual prognosis was significantly associated between trauma and PPV treatment. Conclusions: Good visual outcomes can be achieved for most patients who undergo vitreoretinal surgery after open globe  trauma.
Keywords: Endophthalmitis; Pars plana vitrectomy